Self‐Supporting Graphene Hydrogel Film as an Experimental Platform to Evaluate the Potential of Graphene for Bone Regeneration. (18th February 2013) - Lu, Jiayu; He, Yu‐Shi; Cheng, Chi; Wang, Yi; Qiu, Ling; Li, Dan; Zou, Derong
Abstract Graphene, a two dimensional carbonaceous material possessing a range of extraordinary properties, is considered promising for biomedical applications. Here, a simple form of graphene‐based bulk material–self‐supporting graphene hydrogel (SGH) film is used as a suitable platform to study the intrinsic properties of graphene both in vitro and in vivo. The free‐standing film show good cell adhesion, spreading, and proliferation. Films are implanted into subcutaneous sites of rats, and produce minimal fibrous capsule formation, and mild host tissue response in vivo. New blood vessel formation is also seen. The films swell and cracked in vivo, indicating the beginning of degradation. Of particular interest is that the film alone is found to be able to stimulate osteogenic differentiation of stem cells, without additional inducer, both in vitro and in vivo. Thus, this SGH film appears to be highly biocompatible and osteoinductive, demonstrating graphene's potential for bone regenerative medicine.